Transmission Power Control in Mobile Wireless Sensor Networks: Simulation-based Approach - Mohamad Nazim, Jambli; Halikul, Lenando; Kartinah, Zen; Sinarwati, Mohamad Suhaili; Tully, Alan (IEEE, 2012)
Saving energy is a very critical issue in wireless sensor networks (WSNs) because sensor nodes have a severe resource constraints such as lack of processing power and limited in power supply. Since the communication is the most energy consuming activities in WSNs, the power use for transmission or reception of packet should be managed properly. Transmission power control (TPC) technique is one of the techniques to reduce energy consumption which has been widely studied in mobile ad-hoc networks (MANETs). This technique is implemented by adjusting the transmission power in communication between nodes. However, as mobile wireless sensor networks (MWSNs) applications emerge, the unique characteristics of this network such as severe resource constraints and frequent topology change suggest that TPC might be useful to reduce energy consumption in MWSN. Therefore, we investigate the impact of TPC on Ad hoc On-Demand Distance Vector (AODV) routing protocol for MWSNs. AODV is used as a medium of communication to assist the investigation of the effects of TPC in multihop communication in MWSNs. The simulation results show that the implementation of TPC technique has some impact on MWSNs in respect to transmission energy consumption and transmission power level required at low node mobility.